Honey bee network in Africa co-creating a grassroots innovation ecosystem in Africa - Anil K. Gupta; Chintan Shinde; Anamika Dey; Ramesh Patel; Chetan Patel; Vipin Kumar; Mahesh Patel (University of Bonn, Center for Development Research (ZEF), 2019)
This paper presents a case study of the Honey Bee Network's decentralized model for collecting, verifying and disseminating grassroots innovations and provides a roadmap for its replication in Africa. The Honey Bee Network brings together governmental and non-governmental institutions, members of academia, scholars and a large number of volunteers. Through the Network's activities, locallydesigned solutions and traditional knowledge with the potential to be refined and scaled up are scouted and members of the Network work with the innovators to help their ideas reach their commercial or non-commercial potential. The Network has been involved in the sharing of grassroots technology developed in India with Kenya, notably a food processing machine, seed sowing device, and a small tractor. Through these pilot programs, actors at the grassroots had a chance to collaborate and co-design solutions adapted to the Kenyan context. This experience revealed a willingness in Kenya to further invest in grassroots innovation initiatives, and Network members identified many conditions that would make Kenya the right choice for an African network hub, such as a rich traditional knowledge system and institutional willingness and recognition of the dynamism of the informal sector. Lessons from the Network's experience in Kenya and its technology transfer program are collected and turned into recommendations for the development of a sister Network in Africa.
Keywords: O30; O31; O32; O33; O34; O35; 330; grassroots innovation; technology; agriculture; India; Kenya